2014
DOI: 10.1159/000358173
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Complication of Bone Marrow Aspiration and Trephine Biopsy: Arteriovenous Fistula

Abstract: Objective: To report a case of arteriovenous fistula (AVF) following bone marrow aspiration and trephine biopsy. Clinical Presentation and Intervention: A 76-year-old man was diagnosed with acute myeloblastic leukemia. Pain and hematoma were detected in his left leg and hip 4 days after bone marrow aspiration and trephine biopsy. A pelvic arteriography was performed, and a diagnosis of AVF was made. Conclusion: This case shows that clinicians should be aware of AVF, especially in cases with refractory bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Ilhami et al . reported an unexpected complication of bone marrow biopsy of an arteriovenous fistula secondary to injury of the superior gluteal artery, for which successful embolization was achieved with coils [3]. Chamisa reported a fatal retroperitoneal hemorrhage caused by damage to the superior gluteal artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilhami et al . reported an unexpected complication of bone marrow biopsy of an arteriovenous fistula secondary to injury of the superior gluteal artery, for which successful embolization was achieved with coils [3]. Chamisa reported a fatal retroperitoneal hemorrhage caused by damage to the superior gluteal artery.…”
Section: Discussionmentioning
confidence: 99%
“…[2]74 femaleIliolumbar arterySurgeryCompletely recoveredIlhami et al . [3]76 maleSuperior gluteal arteryTranscatheter embolizationCompletely recoveredChamisa [4]29 maleSuperior gluteal arteryTranscatheter embolizationDiedSullivan et al . [5]55 maleSuperior gluteal arteryTranscatheter embolizationCompletely recoveredNeese et al .…”
Section: Introductionmentioning
confidence: 99%
“…Both patients recovered without sequelae. Berber et al 11 detected arteriovenous fistula (AVF) in a 76-year-old man after bone marrow aspiration and biopsy. They suggested that in cases with refractory bleeding AVF should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered a safe procedure with minimal risks. However, numerous cases of neurovascular injury, including post procedure hemorrhage, arteriovenous fistula formation, gluteal compartment syndrome, and pseudoaneurysm formation have been reported . Retroperitoneal hemorrhage is presumed to occur due to penetration of the biopsy needle through the inner ilial cortex and into adjacent vasculature.…”
Section: Introductionmentioning
confidence: 99%